Lignans from The Nepalese Sandal Wood Osyris wightiana Wall ex Wight - Shyaula, Sajan L; Manandhar, Mangala D; Choudhary, Min (Journal of Nepal Chemical Society, 2013)
The crude ethanolic extract of the Nepalese sandal wood, Osyris wightiana Wall ex Wight, was investigated for phytochemical constituents by chromatographic and spectroscopic techniques. The lignans were the first time reported from the genus Osyris. The lignans, (±) lyoniresinol (1), (±) syringaresinol (2) 5,5’-dimethoxylariciresinol (3), and 5-methoxylariciresinol (4) were isolated from dichloromethane fraction. The structures of compounds were identified by using mass and NMR spectroscopic techniques. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8037 Journal of Nepal Chemical Society Vol.28, 2011 Page 24-28 Uploaded date: March 6, 2013